Africa agriculture status report 2015: Youth and agriculture in Sub-Saharan Africa - Ameyaw, David Sarfo (AGRA / CTA, 2015)
Each year, 10 million young Africans enter the continent’s workforce, more than ever before. Although this highlights the great challenge of youth unemployment, it could also be a great opportunity – to encourage youth to be the engine behind the growth of Africa’s agriculture-based economies. Illustrated throughout with tables, boxed examples and graphs, this publication highlights progress encouraging the role of young people in Africa’s socio-economic growth through agriculture. The comprehensive and detailed chapters look at the current status of youth in agriculture, the role of young people in agricultural productivity and entrepreneurship, finance, ICTs and capacity building, and establishing a conducive policy environment for youth engagement.